2022
DOI: 10.1002/lary.30400
|View full text |Cite
|
Sign up to set email alerts
|

Is COVID‐19 to Blame for Sensorineural Hearing Deterioration? A Pre/Post COVID‐19 Hearing Evaluation Study

Abstract: Objectives Here, we aimed to (a) determine whether a clinically significant sensorineural hearing loss (SNHL) change could be detected in post‐coronavirus disease (COVID‐19) hearing levels on comparing them with pre‐infection hearing levels after controlling for the effect of age and (b) to identify risk factors, such as hypertension, diabetes, and smoking, which increase the likelihood of hearing loss in COVID‐19 patients. Methods We retrospectively analyzed hearing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Recent studies that employed structured methodological approaches reported absent effect of COVID-19 on hearing. For example, Taitelbaum-Swead et al ( 8 ) reported no difference in hearing sensitivity pre and post-COVID-19 infection (after controlling for age). When considering patients with severe COVID-19 symptoms, Visram et al (in press), also did not identify a difference in auditory function between 57 hospitalized COVID-19 patients and 40 matched non-COVID hospitalized controls when participants' hearing function was thoroughly investigated using lab-based behavioral and physiological measures.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies that employed structured methodological approaches reported absent effect of COVID-19 on hearing. For example, Taitelbaum-Swead et al ( 8 ) reported no difference in hearing sensitivity pre and post-COVID-19 infection (after controlling for age). When considering patients with severe COVID-19 symptoms, Visram et al (in press), also did not identify a difference in auditory function between 57 hospitalized COVID-19 patients and 40 matched non-COVID hospitalized controls when participants' hearing function was thoroughly investigated using lab-based behavioral and physiological measures.…”
Section: Introductionmentioning
confidence: 99%